2018
DOI: 10.2217/cer-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and economic impact of paliperidone palmitate versus oral atypical antipsychotics in a Medicare population

Abstract: Compared with patients using oral atypical antipsychotics, PP had lower hospitalizations and medical costs with greater medication adherence accompanied by higher pharmacy costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Similar German studies comparing persistence of LAIs and OAPs are unavailable. However, our results are in line with observational studies of varying sample sizes conducted in the USA [20,21,25,29,43]. Greene et al [20] analyzed Medicaid data and reported that a greater proportion of LAI users than OAP users had PDC ≥ 0.8 after a year of follow-up (33.9% vs. 25.5%; p < 0.001).…”
Section: Time To End Of Therapysupporting
confidence: 89%
See 2 more Smart Citations
“…Similar German studies comparing persistence of LAIs and OAPs are unavailable. However, our results are in line with observational studies of varying sample sizes conducted in the USA [20,21,25,29,43]. Greene et al [20] analyzed Medicaid data and reported that a greater proportion of LAI users than OAP users had PDC ≥ 0.8 after a year of follow-up (33.9% vs. 25.5%; p < 0.001).…”
Section: Time To End Of Therapysupporting
confidence: 89%
“…Pilon et al [25] reported the odds of being adherent to the prescribed treatment (PDC ≥ 0.8) were higher among users of secondgeneration antipsychotic (SGA) LAIs compared with OAP users (odds ratio [OR] 1.28, 95% CI 1.18-1.40; p < 0.001). Joshi et al [29] reported similar results as users of paliperidone palmitate LAI were more adherent than OAP users (PDC ≥ 0.8: 48.1% vs. 32.6%; p < 0.001).…”
Section: Covariatesmentioning
confidence: 64%
See 1 more Smart Citation
“…Exceptions were a study (Mohamed et al 2009) reporting lower medication adherence and three studies (Schreiner et al 2014;Stankovi c & Ille 2013;Weiden et al 2012) finding no differences in LAI compared with oral users. Eight studies (Anderson et al 2017;Greene et al 2018;Joshi et al 2018aJoshi et al , 2018cLefebvre et al 2017;Manjelievskaia et al 2018;Pilon et al 2017bPilon et al , 2017cYan et al 2018;Young-Xu et al 2016) in the pooled analysis showed no differences between LAIs and orals regarding the proportion of patients that had 80% or more PDC (n = 59042, 95% CI = 0.804-3.695, P < 0.162; s 2 = 1.142, I 2 = 94.605%, Q = 129.759, df = 7, P < 0.001) (Figure 2). The true effect in 95% of all comparable populations fell within the prediction interval 0.16-23.50 (see supplemental materials).…”
Section: Medication Adherencementioning
confidence: 99%
“…Changes in healthcare costs were reported in 15 studies (Baser et al 2015;Fan et al 2018;Joshi et al 2018aJoshi et al , 2018cLafeuille et al 2015Lafeuille et al , 2018Lefebvre et al 2017;Manjelievskaia et al 2018;Moore et al 1998;Pesa et al 2015;Pilon et al 2017bPilon et al , 2017cXiao et al 2015Xiao et al , 2016Young-Xu et al 2016) (Table 5).…”
Section: Healthcare Costsmentioning
confidence: 99%